From Endometriosis to Pregnancy: Which is the "Road-Map"?. Issue 4 (October 2017) - Zupi, Errico; De Felice, Giovanna; Conway, Francesca; Martire, Francesco; Exacoustos, Caterina; Centini, Gabriele; Patrizi, Lodovico; Piccione, Emilio; Lazzeri, Lucia
In the last decade, pregnancy was considered as a therapeutic period for patients affected by endometriosis and painful symptoms. However, several studies have taken into consideration how endometriosis affects pregnancy achievement and pregnancy development, including obstetric complications. The adverse effects of endometriosis on the development of pregnancy include miscarriage, hypertensive disorders and pre-eclampsia, placenta previa, obstetric hemorrhages, preterm birth, small for gestational age, and adverse neonatal outcomes. The aim of this review is to analyze the current literature regarding the relationship between different forms of endometriosis (endometrioma, peritoneal endometriosis, deep endometriosis) and infertility, and the impact of endometriosis on pregnancy outcomes.